Literlature of Isan Jataka : Identity reflection of Belief, Way of life, Tradition and Rite. - นิลวรรณาภา, ราชันย์; ประเสริฐสังข์, พิพัฒน์ (Journal for Developing the Social and Community, 2016)
This research aims to study I-san Jataka Literature by Ariyanuwut Khammajaree, 22 stories. The importance of issues is reflects character, social and cultural is showing in stories. The research findings that : Identity reflection of belief about of superstition was a ghost and god in I-san local, Belief about ghost and god in I-san local related I – san people from be born until die. Belief about I-san local astrology is knowledge from ancestor to the next generation and now I-san people apply that for everyone be sustain. Belief about dream and presage is control the way of I-san people life. Belief about religion included Buddhism religion and Brahmanism. Belief about Buddhism religion in I-san Jataka Literature includes belief about merit and demerit, belief about hell and heaven, belief about circle of life. That is to say when the death come a person who has a goodness can reborn in the future life. Belief about Brahmanism in I-san Jataka Literature included, belief about brahma’s god, belief about incantation and superstition. Identity reflection of the way of life, Tradition and Rite in Isan Jataka literature. includes refer to cultures, nature, animal and people, how people, nature and animal can live together. The old family of I-san people in Isan Jataka Literature includes family with a monogamy and family mixed that is to say man will work and take care their family. The man will have power more than wife. Most of career was farmer, I-san people leave at the country side so people will have many lands for agriculture. The career for contact with another business is Nai – Houi. The reflex of I-san food is always related people with naturel. The reflex of culture of I-san homestead in the stories writing about, how to live and relationship of people with nature including people change character about habit, architecture take it easy. Culturel of I-san musical performances and amusement is showing that in the I-san traditions and ceremonies. Culturel of consume goods includes an appliance in household includes “Kongkhao” “Kadong” “Kabian” “Takaa”, appliance of catch animal includes “Baet” “Sai” “Khong” “Whing” “Uan” “Daang”. All of appliance arm from I-san local wisdom. The identity of I-san local time call includes, local name of months count , local name of day count, local name of time count. Culture of I-san traditions and rituals includes, traditions and rituals in the life, traditions and rituals of the year.